ปัจจัยที่สัมพันธ์กับอำนาจควบคุมตนของนักเรียนมัธยมศึกษาปีที่ 4 - ศิวะพร เทพภิบาล (จุฬาลงกรณ์มหาวิทยาลัย, 2003)
The purpose of this research was to study factors related to locus of control of mathayomsuksa-4 students. 1,134 subjects of this research were randomized from mathayomsuksa 4 students enrolling in 6 public schools. After completing the locus of control inventory (Nowicki & Strickland, 1973), the subjects were divided into two groups : 150 internal locus of control group (scores from percentile 1st-20th), 150 external locus of control group (scores from percentile 80th-100th). Then, the two groups were assigned to complete the self-esteem inventory (Coopersmith, 1967) and Cornell Critical Thinking test Level X (Ennis & Millman, 1985). The data were analysed by stepwise discriminant analysis and Wilks s lambda method was used as the entry criterion. The result is as follows : The 2 factors : Self-esteem and critical thinking are able to account for the variance of group membership between internal and external locus of control of mathayomsuksa 4 students 62.4 percent : self-esteem (Ci=0.871) and critical thinking (Ci=0.518) And the percentage of effectiveness in predicting group membership of locus of control of mathayomsuksa 4 students is 90.3.